A Comparison of Muon Flux Models at Sea Level for Muon Imaging and Low Background Experiments - Su, Ning; Liu, Yuanyuan; Wang, Li; Wu, Bin; Cheng, Jianping (Frontiers in Energy Research, 2021)
Cosmic-ray muons are a type of natural radiation with high energy and a strong penetration ability. The flux distribution of such particles at sea level is a key problem in many areas, especially in the field of muon imaging and low background experiments. This paper summarizes the existing models to describe sea-level muon flux distributions. According to different means used, four parametric analytical models and one Monte Carlo model, which is referred to as CRY, are selected as typical sea-level muon flux distribution models. Then, the theoretical values of sea-level muon fluxes given by these models are compared with the experimental sea-level muon differential flux data with kinetic energy values in the range of 1–1,000 GeV in the directions of zenith angles 0° and 75°. The goodness of fit of these models to the experimental data was quantitatively calculated by Pearson’s chi-square test. The results of the comparison show that the commonly used Gaisser model overestimates the muon flux in the low-energy region, while the muon flux given by the Monte Carlo model CRY at the large zenith angle of 75° is significantly lower than that of the experimental data. The muon flux distribution given by the other three parametric analytical models is consistent with the experimental data. The results indicate that the original Gaisser model is invalid in the low energy range, and CRY apparently deviates at large zenith angles. These two models can be substituted with the muon flux models given by Gaisser/Tang, Bugaev/Reyna, and Smith and Duller/Chatzidakis according to actual experimental conditions.